2016
DOI: 10.1080/15548627.2016.1151580
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy receptor FUNDC1 regulates mitochondrial dynamics and mitophagy

Abstract: Mitochondrial fragmentation due to imbalanced fission and fusion of mitochondria is a prerequisite for mitophagy, however, the exact "coupling" of mitochondrial dynamics and mitophagy remains unclear. We have previously identified that FUNDC1 recruits MAP1LC3B/LC3B (LC3) through its LC3-interacting region (LIR) motif to initiate mitophagy in mammalian cells. Here, we show that FUNDC1 interacts with both DNM1L/DRP1 and OPA1 to coordinate mitochondrial fission or fusion and mitophagy. OPA1 interacted with FUNDC1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
309
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(317 citation statements)
references
References 26 publications
6
309
0
2
Order By: Relevance
“…36 Since FUNDC1’s localization in MAMs have been reported in HeLa cells 29, 30 , several steps were taken to determine if FUNDC1’s effects on intracellular calcium homeostasis in cardiomyocytes are dependent on MAMs formation. First, we detected FUNDC1 subcellular localization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Since FUNDC1’s localization in MAMs have been reported in HeLa cells 29, 30 , several steps were taken to determine if FUNDC1’s effects on intracellular calcium homeostasis in cardiomyocytes are dependent on MAMs formation. First, we detected FUNDC1 subcellular localization.…”
Section: Resultsmentioning
confidence: 99%
“…28 Recent studies report that FUNDC1 localizes in MAMs of HeLa cells. 29, 30 However, whether or not FUNDC1 regulates MAMs formation and influences MAMs function is unknown. Furthermore, the expression of Fundc1 in cardiac tissues, as well as its functions remain poorly studied.…”
Section: Introductionmentioning
confidence: 99%
“…The integral mitochondrial outermembrane protein FUNDC1 was originally reported as a major player in hypoxia-induced mitophagy [38]. FUNDC1 can regulate mitophagy both through recruitment of LC3 via its typical LC3-binding motif Y(18)xxL(21), and by regulation of mitochondrial dynamics through interaction with fission and fusion proteins (DNM1L/DRP1 and OPA1, respectively) [38, 39]. MUL1 (mitochondrial ubiquitin ligase 1) is an E3 protein ligase that localizes onto the mitochondrial outer membrane during mitophagy [40].…”
Section: Overview Of Mitophagy Pathwaysmentioning
confidence: 99%
“…FUNDC1 interacts with both DRP1 and OPA1 to regulate mitochondrial fission or fusion and mitophagy. They have also showed that OPA1 interacts with FUNDC1 via its Lys70 residue and mutation of K70 to Ala (A) but not Arg (R) abolished the interaction suggesting FUNDC1 role in the regulation of mitochondrial dynamics and quality control (Chen et al, 2016). Hypoxia appears to be an inducer of FUNDC1 mediated fission by mediating loss of its interaction with ER protein CANX (Wu et al, 2016).…”
Section: Mitochondrial Stress Responsementioning
confidence: 99%